Attempts to preserve and visualize protein corona on the surface of biological nanoparticles in blood serum using photomodification - Julia E. Poletaeva; Anastasiya V. Tupitsyna; Alina E. Grigor’eva; Ilya S. Dovydenko; Elena I. Ryabchikova (Beilstein Journal of Nanotechnology)
A protein corona is present on any nanoparticle (NP) entering biological fluids; however, the existence of a natural protein corona on natural NPs has not been experimentally confirmed. We used our previously developed photomodification method to fix the natural corona on “biological nanoparticles” (bio-NPs) in fetal bovine serum and newborn bovine serum; native sera served as a control. To isolate photomodified bio-NPs, we used ultracentrifugation (UC), sucrose gradient (12%, 30%, and 50%), and sucrose cushion (30%) methods. Isolated bio-NPs were visualized using transmission electron microscopy. The results showed that a protein corona is present on extracellular vesicles and lipoproteins isolated by UC. The isolation of bio-NPs through sucrose gradient or cushion did not preserve the protein corona. At the same time, we observed signs of a negative effect of the sucrose gradient on bio-NPs of intact and photomodified serum; when isolating these particles on a sucrose cushion, no negative effects were observed. We believe that the data we present will be useful to researchers using sucrose solutions to isolate bio-NPs and working on the properties of the protein corona. In this work, we have obtained direct images of a “natural” protein corona on natural bio-NPs of blood serum for the first time